2013
DOI: 10.1111/ctr.12224
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter review of liver transplant for hepatitis B‐related liver disease: disparities in gender and ethnicity

Abstract: Orthotopic liver transplantation (OLT) is the preferred treatment for selected patients with hepatitis B virus (HBV)-related liver disease. This study aimed to (i) define long-term outcomes following OLT for HBV; (ii) to quantify the incidence of HBV recurrence (rHBV) as it relates to anti-HBV treatment; and (iii) to determine outcomes for specific patient subgroups. We performed a retrospective chart review of 738 patients undergoing OLT between 1985 and 2010 at seven US transplant centers and divided the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
0
8
0
1
Order By: Relevance
“…Because of the heterogeneous nature of HBV therapies over the time period of this study, we divided the patients into 3 eras: (1) 1985‐1994, (2) 1995‐2004, and (3) 2005‐2010. Each era was unique and represented a dominant HBV therapy …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the heterogeneous nature of HBV therapies over the time period of this study, we divided the patients into 3 eras: (1) 1985‐1994, (2) 1995‐2004, and (3) 2005‐2010. Each era was unique and represented a dominant HBV therapy …”
Section: Methodsmentioning
confidence: 99%
“…Previous research suggests that the successful treatment of HBV is associated with improved survival and a reduction in HCC recurrence after transplantation. Observational studies suggest a link between the reemergence of HBV and HCC recurrence in the posttransplant setting . Whether the combination of HBIG and antivirals has a direct antineoplastic effect that is distinct from the suppression of viral replication is not known.…”
mentioning
confidence: 99%
“…A study from 2009, including 274 patients, suggested comparable post-transplant outcomes for African Americans when compared to other racial groups [28]. A more contemporary study of 738 patients from 10 academic centers, suggested that African Americans had higher rates of mortality, a finding for which the reasoning remains unclear [29]. …”
Section: Towards Eliminating Viral Hepatitismentioning
confidence: 99%
“…Differences in outcome after transplant may be biologically driven and may also be related to medical compliance. Blacks and women with HBV had worse long-term outcomes post-transplant compared to other races[ 91 ]. Recurrence of HBV was significant for Blacks even ten years post liver transplant, affecting the survival rate.…”
Section: Liver Transplantationmentioning
confidence: 99%